Integrity levels of Chinese college students: An analysis of influencing factors - Li, Xiaohong; Zhao, Jin; Yan, Wenfan (Frontiers in Education, 2022)
This study explores Chinese college students' integrity status and the influencing factors to understand the best practices of Chinese colleges and universities on the issue of integrity cultivation, which is critical for the quality of Chinese higher education. A mixed method combining the quantitative and qualitative data were applied. Respondents from 63 Chinese higher education institutions to the questionnaire were received, which suggested the medium level of Chinese college students' integrity. Compared with the integrity education in western countries, Chinese higher education institutions pay attention to relationship integrity, financial integrity, and employment integrity in everyday life, in addition to academic integrity. The results of csQCA analysis indicated that the university management played an important role in students' integrity and the main influencing factors are policymaking that is appropriate to students' needs, the platform that caters to students' diversified interests, and the supportive environment for integrity. The interactions among the three factors affect and improve Chinese college students' integrity levels.